Primary Percutaneous Coronary Intervention in a Patient with Haemophilia A. (19th December 2013) - Reddy, S. Ashwin; Hoole, Stephen P.; Besser, Martin W.
Abstract : Haemophilia A is a rare genetic condition leading to coagulation factor VIII deficiency and thus predisposing to bleeding diathesis. Due to advances in treatment, life expectancy of haemophilia A sufferers is increasing, and the incidence and prevalence of coronary artery disease are rising. There have been many reported cases of acute myocardial infarction in such patients, who subsequently undergo elective percutaneous coronary intervention. We present the case of a 55-year-old gentleman presenting with an acute anterior full-thickness myocardial infarction who required emergency primary percutaneous coronary intervention.